The nanoleakage phenomenon: influence of different dentin bonding agents, thermocycling and etching time - Dörfer, Christof; Staehle, Hans Jörg; Wurst, Marcus; Duschner, Heinz; Pioch, Thomas (European journal of oral sciences, 2000)
“Nanoleakage” takes place within the hybrid layer zone of the dentin-composite interface in spaces not occupied by polymerized resin. The purpose of this study was to quantify the amount of nanoleakage in specimens treated with one of six different bonding agents. For one agent, different etching times were used, and for two agents results after thermocycling were obtained.
First published: 25 December 2001
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 19.02.2021